2020
DOI: 10.3390/technologies8040073
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Postprocessing on Wear Resistance of Aerospace Steel Parts Produced by Laser Powder Bed Fusion

Abstract: The paper is devoted to the research of the effect of ultrasonic postprocessing—specifically, the effects of ultrasonic cavitation-abrasive finishing, ultrasonic plastic deformation, and vibration tumbling on surface quality, wear resistance, and the ability of real aircraft parts with complex geometries and with sizes less than and more than 100 mm to work in exploitation conditions. The parts were produced by laser powder bed fusion from two types of anticorrosion steels of austenitic and martensitic grades—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
(96 reference statements)
1
3
0
Order By: Relevance
“…Based on the data contained in Table 1 and literature [4,9,11], it can be confirmed that vibratory machining results in an isotropic structure.…”
Section: Fig 8 Basic Principles Of Vibration Treatmentsupporting
confidence: 62%
See 1 more Smart Citation
“…Based on the data contained in Table 1 and literature [4,9,11], it can be confirmed that vibratory machining results in an isotropic structure.…”
Section: Fig 8 Basic Principles Of Vibration Treatmentsupporting
confidence: 62%
“…Vibratory machining is a finishing process based on chemicalmechanical surface treatment [11,12]. The type of media usedshapes -determines the nature of the process: deburring, grinding or polishing.…”
Section: Methodsmentioning
confidence: 99%
“…• the presence of microcracks due to the shrinkage of the molten material as it solidifies [22,23]; • the presence of surface morphology subjected to repeated focal overheating with the creation of near-track/weld stress zones (heat-affected zones) [24,25]; • active evaporation of the lightest materials from the processing zone [26,27]; • formation of a transitional nanoporous interlayer consisting of more refractory material components [28,29]; • increased formation of brittle structures in the near-surface layer (the formation of second-order secondary compounds on the heating surface, due to the material's active oxidation as a result of the interaction of the molten material of the cutting insert/substrate and coating with the environment) [30]; • splashing of material from the processing zone due to thermal shock [31,32].…”
Section: Cutting Toolmentioning
confidence: 99%
“…The potential applications of LPBF are vast and diverse. In aerospace, for example, the technique can be used to produce lightweight components with complex geometries, reducing the weight of aircraft and improving fuel efficiency [17,18,19,20]. In the medical industry, LPBF can be used to produce customized implants and prosthetics with enhanced biocompatibility [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%